2007
DOI: 10.1021/tx700271j
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Rate of Repair of O6-Alkylguanines in Different Sequence Contexts by O6-Alkylguanine-DNA Alkyltransferase

Abstract: O6-alkylguanine-DNA alkyltransferase (AGT) repairs O6-alkylguanine residues at different rates depending on the identity of the alkyl group as well as the sequence context. To elucidate the mechanism(s) underlying the differences in rates, we examined the repair of five alkyl groups in three different sequence contexts. The kinact and Km values were determined by measuring the rates of repair of oligodeoxynucleotide duplexes containing the O6-alkylguanine residues with various concentrations of AGT in excess. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 35 publications
1
72
0
Order By: Relevance
“…Moreover, eG, unlike heG, is not repaired by the alkyltransferase pathway (28). These surprising differences between the apparently similar eG and heG adducts may be explained by the recent finding that these two adducts exhibit a drastically different partition between the syn and anti conformation of their alkyl moiety (29). Therefore, apparently minor chemical changes appear to trigger major biological consequences.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, eG, unlike heG, is not repaired by the alkyltransferase pathway (28). These surprising differences between the apparently similar eG and heG adducts may be explained by the recent finding that these two adducts exhibit a drastically different partition between the syn and anti conformation of their alkyl moiety (29). Therefore, apparently minor chemical changes appear to trigger major biological consequences.…”
Section: Resultsmentioning
confidence: 99%
“…As stated previously,t his drastic difference imparted by the presence of the phosphodiester linkagem ay likely be the result of the alkylene linkersf ound in GpG4 and GpG7 adopting lessr eactive conformations,w hich has been proposed for other O 6 -alkylated-dG lesions. [39] In our previous report of the repair of duplexesc ontaining the GG4 and GG7 IaCL by hAGT,w ep roposed that the phosphorylation of the damaged strand occurred at the 5'-terminus of the oligomer.Am ore detailed analysis of the repair event revealed that T4 PNK is capable of phosphorylating the internal 5'-hydroxyl group as well( see the Supporting . To validate that T4 PNKc ould in fact phosphorylate both positions, T4 PNK and at hree-fold excess of ATPw ere incubated with either GG4 or GG7.M ass spectral analysis revealed the presence of mono-a nd bis-phosphorylated products (see Supporting Figures 21-22).…”
mentioning
confidence: 97%
“…O6mG lesions have one of the highest mutagenic potentials of the lesions produced by monofunctional methylating agents, while N7-alkylguanine and N3-alkyladenine adducts are more likely to be cytotoxic if they go unrepaired (12). O6eG lesions such as those produced by DEN are repaired by human MGMT at ~1/10 to 1/150 th of the rate as for O6mG lesions produced by MNU (26, 27). Therefore, mice were treated with MNU to analyze the effects of an alkylating agent that produces DNA damage that is efficiently repaired by MGMT, namely O6mG.…”
Section: Resultsmentioning
confidence: 99%